New worlds from old texts : revisiting ancient space and place - Barker, Elton; Barker, Elton; Bouzarovski, Stefan; Bouzarovski, Stefan; Isaksen, Leif; Isaksen, Leif; Pelling, Christopher; Pelling, Christopher (Oxford University Press, 2016)
Written by a highly interdisciplinary range of contributors, 'New Worlds from Old Texts' explores ancient Greek perceptions of space and how they may have differed from the modern cartographic view